Application of α-MoO3-modified graphene in lithium-ion batteries and lithium-ion batteries

By using α-MoO3-modified graphene as a conductive agent in lithium-ion batteries, the problem of short cycle life of traditional lithium-ion batteries is solved, and higher capacity retention and better safety performance are achieved.

CN105826595BActive Publication Date: 2025-04-25SHENZHEN BAK POWER BATTERY CO LTD

Patent Information

Application Number
CN201510006198.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2015-01-06
Publication Date
2025-04-25
Estimated Expiration
2035-01-06

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have short cycle life and are difficult to meet the requirements of high capacity, large-magnification and long life.

Method used

α-MoO3-modified graphene is used as the conductive agent for the positive electrode of lithium-ion batteries to enhance the conductivity of the battery.

Benefits of technology

The cycle life of lithium-ion batteries is significantly improved. After circulating 300 times under normal temperature conditions, the capacity retention rate is increased by about 15%, and the charge and discharge polarization is reduced, which improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN105826595B_ABST
    Figure CN105826595B_ABST
Patent Text Reader

Abstract

The present invention discloses an application of α-MoO3-modified graphene in a lithium-ion battery and a lithium-ion battery. The present invention uses α-MoO3-modified graphene as a conductive agent for a positive electrode, which can enhance the conductivity of the battery and significantly improve the cycle life of the battery. Compared with a lithium-ion battery made of a conventional conductive agent, a lithium-ion battery made of the α-MoO3-modified graphene of the present invention as a conductive agent for a positive electrode has a capacity retention rate increased by about 15% after 300 cycles at room temperature. In addition, the lithium-ion battery of the present invention can reduce charge and discharge polarization, improve battery safety, and has broad market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to the application of α-MoO3-modified graphene (α-MoO3-graphene nanosheets composites, MG) in lithium ion batteries and lithium ion batteries. Background Art

[0002] Promoting the industrialization of notebooks, mobile power supplies, electric bicycles, electric tools, and electric vehicles has become the entry point for China's industrial restructuring and leapfrog development. One of the key technologies for notebooks, mobile power supplies, electric bicycles, electric tools, and electric vehicles is to develop and manufacture batteries that meet safety and environmental protection requirements, have high capacity, high rate, and long life. Lithium-ion batteries have become the first choice for notebooks, mobile power supplies, electric bicycles, electric tools, and electric vehicles due to their obvious advantages in specific power, specific energy, and cycle performance.

[0003] However, traditional lithium-ion batteries usually use small particle carbon black (Super P), carbon fiber (VGCF) and other traditional conductive agents as conductive materials for the positive electrode. These conductive materials often fail to meet the expected requirements in terms of specific power, specific energy and cycle performance, especially the battery cycle life is difficult to have a major breakthrough, resulting in difficulty in improving the overall performance of the battery. Therefore, the development of a conductive material that can bring a long cycle life to lithium-ion batteries is of great value for improving the performance of lithium-ion batteries. Summary of the invention

[0004] The present invention provides application of α-MoO3-modified graphene in lithium ion batteries. The α-MoO3-modified graphene is used as a conductive agent for the positive electrode of the lithium ion battery, which can enhance the conductivity of the battery and significantly improve the cycle life of the battery.

[0005] On this basis, the present invention also provides a lithium ion battery positive electrode slurry, a positive electrode sheet and a lithium ion battery made using α-MoO3-modified graphene, as well as their preparation methods.

[0006] According to a first aspect of the present invention, the present invention provides use of α-MoO3-modified graphene as a conductive agent in a lithium ion battery.

[0007] The above-mentioned conductive agent refers to a conductive agent for a positive electrode of a lithium ion battery.

[0008] According to a second aspect of the present invention, the present invention provides a positive electrode slurry for a lithium ion battery, wherein the positive electrode slurry comprises α-MoO3-modified graphene as a conductive agent.

[0009] As a preferred embodiment of the present invention, the content of the α-MoO3-modified graphene in the positive electrode slurry is 0.6-1.0% by weight.

[0010] According to the third aspect of the present invention, the present invention provides a method for preparing the positive electrode slurry of a lithium ion battery according to the second aspect, the preparation method comprising the following steps: adding 16-20% nitrogen methyl pyrrolidine into a glue making pot according to the mass ratio, evacuating, replenishing nitrogen, adding 0.9-1.5% positive electrode adhesive, stirring, adding 0.6-1.0% α-MoO3-modified graphene conductive agent, stirring and evacuating to prepare a conductive glue having a viscosity of 400-1000MPa·s and a solid content of 4.0-5.0%, then adding positive electrode active material, stirring and evacuating again to prepare a slurry having a discharge viscosity of 1900-3000MPa·s and a solid content of 70-80%, filtering with a filter screen to prepare a positive electrode slurry.

[0011] As a preferred embodiment of the present invention, the positive electrode binder is polyvinylidene fluoride (PVDF);

[0012] Preferably, the positive electrode active material is selected from lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, where 0<x<1, 0<y<1, 0<x+y<1), lithium nickel cobalt aluminum oxide (LiNi x Co (1-x-y) Al y O2, wherein 0<x<1, 0<y<1, 0<x+y<1) is one or a combination of two or more thereof.

[0013] According to a fourth aspect of the present invention, the present invention provides a positive electrode sheet made using the positive electrode slurry for a lithium-ion battery according to the second aspect.

[0014] According to a fifth aspect of the present invention, the present invention provides a lithium ion battery made using the lithium ion battery positive electrode slurry described in the second aspect.

[0015] According to a sixth aspect of the present invention, the present invention provides a method for preparing the lithium ion battery according to the fifth aspect, the preparation method comprising the following steps:

[0016] (1) Preparation of positive electrode slurry: according to the mass ratio, 16-20% of nitrogen methyl pyrrolidine is added to a glue making pot, vacuumed, supplemented with nitrogen, 0.9-1.5% of positive electrode binder is added, stirred, 0.6-1.0% of α-MoO3-modified graphene conductive agent is added, stirred and vacuumed to prepare a conductive glue with a viscosity of 400-1000 MPa·s and a solid content of 4.0-5.0%, and then the positive electrode active material is added, stirred and vacuumed again to prepare a slurry with a discharge viscosity of 1900-3000 MPa·s and a solid content of 70-80%, and filtered through a filter to prepare a positive electrode slurry;

[0017] (2) Preparation of negative electrode slurry: According to the mass ratio, 90-95% of negative electrode active material, 1-2% of conductive carbon black, 1-2% of sodium carboxymethyl cellulose and the balance of deionized water are mixed, stirred, 3-5% of negative electrode binder is added, and stirred again to prepare a slurry with a discharge viscosity of 1300-2300 MPa·s and a solid content of 50-60%, and filtered through a filter to prepare a negative electrode slurry;

[0018] (3) Preparation of positive and negative electrode sheets: coating the positive electrode slurry on aluminum foil and coating the negative electrode slurry on copper foil, pressing them with a roller press, cutting them into positive and negative electrode sheets of predetermined width and length, and drying them;

[0019] (4) Cell winding: stacking the positive electrode sheet, the separator and the negative electrode sheet in order and winding them into a cell using a winding machine;

[0020] (5) The rolled battery cell is placed into a shell, and electrolyte is injected into the shell to package it into a lithium-ion battery.

[0021] As a preferred embodiment of the present invention, the positive electrode binder in step (1) is polyvinylidene fluoride;

[0022] Preferably, the positive electrode active material in step (1) is selected from lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, where 0<x<1, 0<y<1, 0<x+y<1), lithium nickel cobalt aluminum oxide (LiNi x Co (1-x-y) Al y O2, wherein 0<x<1, 0<y<1, 0<x+y<1) is one or a combination of two or more;

[0023] Preferably, after adding the positive electrode active material in step (1), the temperature of the slurry is controlled to be 20-45° C.;

[0024] Preferably, after adding 3-5% of the negative electrode binder in step (2), the temperature of the slurry is controlled to be 20-40° C.;

[0025] Preferably, the negative electrode binder in step (2) is a styrene-butadiene rubber binder;

[0026] Preferably, the negative electrode active material in step (2) is selected from one or both of natural graphite and artificial graphite.

[0027] As a preferred embodiment of the present invention, the thickness of the aluminum foil in step (3) is 12 to 18 μm;

[0028] Preferably, the single-sided surface density of the positive electrode slurry coated on the aluminum foil in step (3) is 200-250 g / m 2 , the upper and lower deviations are allowed to be 3g / m 2 ; Double-sided density is 400~500g / m 2 , the upper and lower deviations are allowed to be 5g / m 2 ;

[0029] Preferably, the thickness of the copper foil in step (3) is 7 to 11 μm;

[0030] Preferably, the single-sided surface density of the negative electrode slurry coated on the copper foil in step (3) is 10 to 15 g / m 2 , the upper and lower deviations are allowed to be 3g / m 2 ; Double-sided surface density is 20-30g / m 2 , the upper and lower deviations are allowed to be 5g / m 2 ;

[0031] Preferably, the thickness of the positive electrode sheet pressed by the roller press in step (3) is 135-170 μm, with an upper and lower deviation of 2 μm allowed; the thickness of the negative electrode sheet is 150-175 μm, with an upper and lower deviation of 2 μm allowed;

[0032] Preferably, the electrolyte in step (5) is an electrolyte containing LiPF6.

[0033] The present invention uses α-MoO3-modified graphene as a conductive agent for the positive electrode, which can enhance the conductivity of the battery and significantly improve the cycle life of the battery. Compared with lithium-ion batteries made with conventional conductive agents, the lithium-ion battery made with the α-MoO3-modified graphene of the present invention as a conductive agent for the positive electrode has a capacity retention rate increased by about 15% after 300 cycles at room temperature. In addition, the lithium-ion battery of the present invention can reduce charge and discharge polarization, improve battery safety performance, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1The capacity retention curves of Example 1 and Comparative Example 1 of the present invention after 300 charge and discharge cycles at room temperature (25° C.) are shown;

[0035] Figure 2 The capacity retention curves of Example 2 and Comparative Example 2 of the present invention after 300 charge and discharge cycles at room temperature (25° C.) are shown;

[0036] Figure 3 The capacity retention curves of Example 3 and Comparative Example 3 of the present invention after 300 charge and discharge cycles at room temperature (25° C.) are shown. DETAILED DESCRIPTION

[0037] The present invention will be further described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0038] The key to the present invention is that the inventors use α-MoO3-modified graphene instead of conventional positive electrode conductive agents to prepare lithium-ion batteries, and surprisingly found that the cycle life of the prepared lithium-ion batteries is significantly improved.

[0039] α-MoO3-modified graphene is a new type of material that can be used in capacitors. The preparation method of the graphene can be referred to the literature (One-step molybdate ion assisted electrochemical synthesis of α-MoO3-decorated graphene sheets and its potential applications, Journal of Materials Chemistry, 2011 (21), 15009-15014).

[0040] The technical solution of the present invention is described in detail below through examples and comparative examples. It should be understood that these descriptions are not restrictive, and the protection scope of the present invention is as defined by the appended claims.

[0041] Example 1

[0042] (1) According to the mass ratio, 16% nitrogen methyl pyrrolidine (NMP) was added into the glue making pot, vacuumed (-0.08 to -0.1 MPa), supplemented with nitrogen (pressure ≥ 0.1 MPa), added with 1.2% PVDF adhesive, stirred for 30 min, 1800-2200 r / min, added with 1.0% MG conductive agent (α-MoO3-modified graphene), stirred for 60 min, and vacuumed for 30 min (vacuum degree greater than -0.09 MPa), and the conductive glue was prepared. The viscosity of the conductive glue was 900 MPa·s and the solid content was 4.5%;

[0043] (2) Adding the positive electrode active material lithium cobalt oxide (LiCoO2), stirring for 120 to 150 minutes, and evacuating (-0.09 MPa); controlling the slurry temperature to 20 to 45°C, wiping the homogenizing pot with alcohol when the slurry temperature rises too high, adding cooling water or reducing the speed to prepare a slurry with a discharge viscosity of 2000 MPa·s and a solid content of 70 to 80%. After stirring, the slurry is filtered through a 150-mesh filter, and the positive electrode slurry is prepared;

[0044] (3) According to the mass ratio, 93% of natural graphite, a negative electrode active material, 2% of conductive carbon black, 2% of sodium carboxymethyl cellulose and deionized water were stirred for 300 minutes, 4% of styrene-butadiene rubber as a binder was added, and stirred for 60 minutes (vacuum degree -0.09 MPa), and the slurry temperature was controlled at 20-40°C to prepare a slurry with a discharge viscosity of 1800 MPa·s and a solid content of 50-60%. After stirring, the slurry was filtered through a 150-mesh filter to complete the preparation of the negative electrode slurry;

[0045] (4) Apply the positive electrode slurry on 12-18 μm aluminum foil and control the single-sided surface density to 200-250±3 g / m 2 , double-sided density is 400~500±5g / m 2 ; Apply the negative electrode slurry on the copper foil of 7-11μm, and control the single-sided surface density to 10-15±3g / m 2 , double-sided density is 20~30±5g / m 2 ;

[0046] (5) Pressing the positive and negative electrode sheets by a roller press, controlling the thickness of the positive electrode to be 135-170±2 μm and the thickness of the negative electrode to be 150-175±2 μm;

[0047] (6) Cut the positive and negative electrode sheets into 58 mm wide and 700 mm long positive electrode sheets and 60 mm wide and 800 mm long negative electrode sheets;

[0048] (7) Place the cut positive and negative electrode sheets in an oven for drying;

[0049] (8) Using a winding machine, the positive electrode sheet, the separator, and the negative electrode sheet are rolled into a battery cell in sequence;

[0050] (9) Place the rolled battery cell into a shell, inject electrolyte (LiPF6 / EC / DMC) into the shell, and package it into a battery cell;

[0051] (10) After the battery cell has been left for 12 hours, it is first charged at a constant current and constant voltage of 0.2C for 500 minutes, and then the single cell is left at a high temperature of 45°C for 72 hours;

[0052] (11) After the battery cell is cooled to room temperature, it is first charged to 4.2V at a constant current and voltage of 0.5C, with a cut-off current of 0.01C, then discharged to 3.0V at a constant current of 0.2C, and then charged to half power at a constant current and voltage of 0.5C.

[0053] Example 2

[0054] (1) According to the mass ratio, 18% nitrogen methyl pyrrolidine (NMP) was added into the glue making pot, vacuumed (-0.08 to -0.1 MPa), supplemented with nitrogen (pressure ≥ 0.1 MPa), added with 1.5% adhesive PVDF, stirred for 45 min, 1800-2200 r / min, added with 0.8% MG conductive agent (α-MoO3-modified graphene), stirred for 70 min, and vacuumed for 30 min (vacuum degree greater than -0.09 MPa), and the conductive glue was prepared. The viscosity of the conductive glue was 1000 MPa·s and the solid content was 5.0%;

[0055] (2) Adding positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), stirred for 120-150min, and vacuumed (-0.09MPa); the slurry temperature was controlled to be 20-45°C. When the slurry temperature was high, the homogenizing pot could be wiped with alcohol, cooling water could be added or the speed could be reduced to prepare a slurry with a discharge viscosity of 3000MPa·s and a solid content of 70-80%. After stirring, the slurry was filtered through a 150-mesh filter, and the positive electrode slurry was prepared;

[0056] (3) According to the mass ratio, 95% of natural graphite, a negative electrode active material, 1.5% of conductive carbon black, 1% of sodium carboxymethyl cellulose and deionized water were stirred for 300 minutes, 3% of styrene-butadiene rubber as a binder was added, and the mixture was stirred for 60 minutes (vacuum degree -0.09 MPa), and the slurry temperature was controlled at 20-40°C to prepare a slurry with a discharge viscosity of 1300 MPa·s and a solid content of 50-60%. After stirring, the slurry was filtered through a 150-mesh filter to complete the preparation of the negative electrode slurry;

[0057] (4) Apply the positive electrode slurry on 12-18 μm aluminum foil and control the single-sided surface density to 200-250±3 g / m 2 , double-sided density is 400~500±5g / m 2 ; Apply the negative electrode slurry on the copper foil of 7-11μm, and control the single-sided surface density to 10-15±3g / m 2 , double-sided density is 20~30±5g / m 2 ;

[0058] (5) Pressing the positive and negative electrode sheets by a roller press, controlling the thickness of the positive electrode to be 135-170±2 μm and the thickness of the negative electrode to be 150-175±2 μm;

[0059] (6) Cut the positive and negative electrode sheets into 58 mm wide and 700 mm long positive electrode sheets and 60 mm wide and 800 mm long negative electrode sheets;

[0060] (7) Place the cut positive and negative electrode sheets in an oven for drying;

[0061] (8) Using a winding machine, the positive electrode sheet, the separator, and the negative electrode sheet are rolled into a battery cell in sequence;

[0062] (9) Place the rolled battery cell into a shell, inject electrolyte (LiPF6 / EC / DMC) into the shell, and package it into a battery cell;

[0063] (10) After the battery cell has been left for 12 hours, it is first charged at a constant current and constant voltage of 0.2C for 500 minutes, and then the single cell is left at a high temperature of 45°C for 72 hours;

[0064] (11) After the battery cell is cooled to room temperature, it is first charged to 4.2V at a constant current and voltage of 0.5C, with a cut-off current of 0.01C, then discharged to 3.0V at a constant current of 0.2C, and then charged to half power at a constant current and voltage of 0.5C.

[0065] Example 3

[0066] (1) According to the mass ratio, 20% nitrogen methyl pyrrolidine (NMP) was added into the glue making pot, vacuumed (-0.08 to -0.1 MPa), supplemented with nitrogen (pressure ≥ 0.1 MPa), added with 0.9% PVDF adhesive, stirred for 25 min, 1800-2200 r / min, added with 0.6% MG conductive agent (α-MoO3-modified graphene), stirred for 45 min, and vacuumed for 30 min (vacuum degree greater than -0.09 MPa), and the conductive glue was prepared. The viscosity of the conductive glue was 400 MPa·s and the solid content was 4.0%;

[0067] (2) Adding positive electrode active material lithium nickel cobalt aluminum oxide (LiNi 0.85 Co 0.1 Al 0.05 O2), stirred for 120-150min, and vacuumed (-0.09MPa); the slurry temperature was controlled to be 20-45°C. When the slurry temperature was high, the homogenizing pot could be wiped with alcohol, cooling water could be added or the speed could be reduced to prepare a slurry with a discharge viscosity of 1900MPa·s and a solid content of 70-80%. After stirring, the slurry was filtered through a 150-mesh filter, and the positive electrode slurry was prepared;

[0068] (3) According to the mass ratio, 90% of the negative electrode active material artificial graphite, 1% of the conductive carbon black, 1.5% of the sodium carboxymethyl cellulose and deionized water were stirred for 280 minutes, and 5% of the binder styrene-butadiene rubber was added and stirred for 60 minutes (vacuum degree -0.09MPa). The slurry temperature was controlled at 20-40°C to prepare a slurry with a discharge viscosity of 2300MPa·s and a solid content of 50-60%. After stirring, the slurry was filtered through a 150-mesh filter to complete the preparation of the negative electrode slurry;

[0069] (4) Apply the positive electrode slurry on 12-18 μm aluminum foil and control the single-sided surface density to 200-250±3 g / m 2 , double-sided density is 400~500±5g / m 2 ; Apply the negative electrode slurry on the copper foil of 7-11μm, and control the single-sided surface density to 10-15±3g / m 2 , double-sided density is 20~30±5g / m 2 ;

[0070] (5) Pressing the positive and negative electrode sheets by a roller press, controlling the thickness of the positive electrode to be 135-170±2 μm and the thickness of the negative electrode to be 150-175±2 μm;

[0071] (6) Cut the positive and negative electrode sheets into 58 mm wide and 700 mm long positive electrode sheets and 60 mm wide and 800 mm long negative electrode sheets;

[0072] (7) Place the cut positive and negative electrode sheets in an oven for drying;

[0073] (8) Using a winding machine, the positive electrode sheet, the separator, and the negative electrode sheet are rolled into a battery cell in sequence;

[0074] (9) Place the rolled battery cell into a shell, inject electrolyte (LiPF6 / EC / DMC) into the shell, and package it into a battery cell;

[0075] (10) After the battery cell has been left for 12 hours, it is first charged at a constant current and constant voltage of 0.2C for 500 minutes, and then the single cell is left at a high temperature of 45°C for 72 hours;

[0076] (11) After the battery cell is cooled to room temperature, it is first charged to 4.2V at a constant current and voltage of 0.5C, with a cut-off current of 0.01C, then discharged to 3.0V at a constant current of 0.2C, and then charged to half power at a constant current and voltage of 0.5C.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, 1.0% of conventional conductive agent small particle carbon black (SuperP) is used as a positive electrode conductive agent instead of 1.0% of α-MoO3-modified graphene in Example 1. The specific preparation process is as follows:

[0079] (1) According to the mass ratio, 16% nitrogen methyl pyrrolidine (NMP) was added into the glue making pot, vacuumed (-0.08~-0.1mpa), supplemented with nitrogen (pressure ≥0.1Mpa), added 1.2% adhesive PVDF, slow speed 30~40rpm + high speed 1500~2000rpm, stirred for 30min, and then added 1.0% conventional conductive agent small particle carbon black (Super P), slow speed 30-40rpm + high speed 1500-2000rpm, stirring for 60min, and then vacuuming for 30min (vacuum degree greater than -0.09MPa), the conductive glue is prepared, the viscosity is 900MPa·s, the solid content is 4.5%, add positive electrode material lithium cobalt oxide (LiCoO2), stir for 120-150min (stirring speed 1500-2200r / min), the vacuum degree is not higher than -0.09MPa, the slurry temperature is controlled at 20-45°C, when the slurry temperature rises to a high level, the homogenizing pot can be wiped with alcohol, cooling water can be added or the speed can be reduced to prepare a slurry with a discharge viscosity of 2000MPa·s and a solid content of 70-80%, and the slurry after stirring is filtered through a 150-mesh filter, and the positive electrode slurry is prepared;

[0080] (2) According to the mass ratio, 93% of natural graphite, a negative electrode active material, 2% of conductive carbon black, 2% of sodium carboxymethyl cellulose and deionized water were stirred for 300 minutes, 4% of styrene-butadiene rubber binder was added, and stirred for 60 minutes (stirring speed 1800-2200r / min), the vacuum degree was not higher than -0.09MPa, and the slurry temperature was controlled at 20-40°C to prepare a slurry with a discharge viscosity of 1800MPa·s and a solid content of 50-60%. After stirring, the slurry was filtered through a 150-mesh filter to complete the preparation of the negative electrode slurry;

[0081] (3) Apply the positive electrode slurry on 12-18 μm aluminum foil and control the single-sided surface density to 200-250±3 g / m 2 , double-sided density is 400~500±5g / m 2 ; Apply the negative electrode slurry on the copper foil of 7-11μm, and control the single-sided surface density to 10-15±3g / m 2 , double-sided density is 20~30±5g / m 2 ;

[0082] (4) Pressing the positive and negative electrode sheets by a roller press, controlling the thickness of the positive electrode to be 135-170±2 μm and the thickness of the negative electrode to be 150-175±2 μm;

[0083] (5) Cut the positive and negative electrode sheets into 58 mm wide and 700 mm long positive electrode sheets and 60 mm wide and 800 mm long negative electrode sheets;

[0084] (6) Place the cut positive and negative electrodes into an oven for drying.

[0085] (7) Using a winding machine, the positive electrode sheet, the separator, and the negative electrode sheet are rolled into a battery cell in sequence;

[0086] (8) Place the rolled battery cell into a shell, inject electrolyte (LiPF6 / EC / DMC) into the shell, and package it into a battery cell;

[0087] (9) After the battery cell has been left for 12 hours, it is first charged at a constant current and constant voltage of 0.2C for 500 minutes, and then the single cell is left at a high temperature of 45°C for 72 hours;

[0088] (10) After the battery cell is cooled to room temperature, it is first charged to 4.2V at a constant current and voltage of 0.5C, with a cut-off current of 0.01C, then discharged to 3.0V at a constant current of 0.2C, and then charged to half power at a constant current and voltage of 0.5C.

[0089] Comparative Example 2

[0090] The difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, 0.8% of conventional conductive small-particle carbon black (Super P) is used as a positive electrode conductive agent to replace 0.8% of α-MoO3-modified graphene in Example 2.

[0091] Comparative Example 3

[0092] The difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, 0.6% of conventional conductive carbon fiber (VGCF) is used as the positive electrode conductive agent instead of 0.6% of α-MoO3-modified graphene in Example 3.

[0093] The lithium ion batteries obtained in Examples 1-3 and Comparative Examples 1-3 were simultaneously subjected to 300 charge and discharge cycles at room temperature (25°C), and their capacity retention rates are shown in Table 1. The cycle life curves of Example 1 and Comparative Example 1 are shown in Figure 1 As shown; the cycle life curves of Example 2 and Comparative Example 2 are as shown Figure 2 The cycle life curves of Example 3 and Comparative Example 3 are shown as Figure 3 shown.

[0094] Table 1

[0095] Example / Comparative Example Capacity retention after 300 cycles Example 1 96.06% Comparative Example 1 81.11% Example 2 94.79% Comparative Example 2 80.04% Example 3 93.56% Comparative Example 3 80.78%

[0096] The results show that the cycle life of the lithium ion battery obtained in Examples 1-3 is significantly improved compared with that of Comparative Examples 1-3. After 300 cycles at room temperature, the capacity retention rate can be increased by up to about 15%.

[0097] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention.

Claims

1. A method for preparing a positive electrode slurry for a lithium ion battery, characterized in that: The positive electrode slurry contains α-MoO3-modified graphene as a conductive agent, wherein the content of the α-MoO3-modified graphene in the positive electrode slurry is 0.6-1.0% by weight; The preparation method comprises the following steps: adding 16-20% of nitrogen methyl pyrrolidine into a glue making pot according to the mass ratio, evacuating, replenishing nitrogen, adding 0.9-1.5% of a positive electrode binder, stirring, adding 0.6-1.0% of an α-MoO3-modified graphene conductive agent, stirring and evacuating to prepare a conductive glue having a viscosity of 400-1000 MPa·s and a solid content of 4.0-5.0%, then adding a positive electrode active material, stirring and evacuating again to prepare a slurry having a discharge viscosity of 1900-3000 MPa·s and a solid content of 70-80%, filtering with a filter screen to prepare a positive electrode slurry.

2. The preparation method according to claim 1, characterized in that: The positive electrode binder is polyvinylidene fluoride.

3. The preparation method according to claim 1, characterized in that: The positive electrode active material is selected from one or a combination of two or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

4. A method for preparing a lithium ion battery, characterized in that: The lithium-ion battery is made of a lithium-ion battery positive electrode slurry, wherein the positive electrode slurry contains α-MoO3-modified graphene as a conductive agent, wherein the content of the α-MoO3-modified graphene in the positive electrode slurry is 0.6-1.0% by weight; The preparation method comprises the following steps: (1) Preparation of positive electrode slurry: according to the mass ratio, add 16-20% of nitrogen methyl pyrrolidine into a glue making pot, evacuate, replenish nitrogen, add 0.9-1.5% of positive electrode binder, stir, add 0.6-1.0% of α-MoO3-modified graphene conductive agent, stir and evacuate to make a conductive glue with a viscosity of 400-1000 MPa·s and a solid content of 4.0-5.0%, then add positive electrode active material, stir and evacuate again to make a slurry with a discharge viscosity of 1900-3000 MPa·s and a solid content of 70-80%, filter through a filter to make positive electrode slurry; (2) Preparation of negative electrode slurry: according to the mass ratio, 90-95% of negative electrode active material, 1-2% of conductive carbon black, 1-2% of sodium carboxymethyl cellulose and the balance of deionized water are mixed, stirred, 3-5% of negative electrode binder is added, stirred again, and a slurry with a discharge viscosity of 1300-2300 MPa·s and a solid content of 50-60% is prepared, and filtered through a filter to prepare negative electrode slurry; (3) Preparation of positive and negative electrode sheets: coating the positive electrode slurry on aluminum foil and coating the negative electrode slurry on copper foil, pressing them with a roller press, cutting them into positive and negative electrode sheets of predetermined width and length, and drying them; (4) Cell winding: stacking the positive electrode sheet, the separator and the negative electrode sheet in order and winding them into a cell using a winding machine; (5) Place the rolled battery cell into a shell, inject electrolyte into the shell, and package it into a lithium-ion battery.

5. The preparation method according to claim 4, characterized in that: The positive electrode binder in the step (1) is polyvinylidene fluoride.

6. The preparation method according to claim 4, characterized in that: The positive electrode active material in step (1) is selected from one or a combination of two or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

7. The preparation method according to claim 4, characterized in that: After adding the positive electrode active material in step (1), the temperature of the slurry is controlled to be 20-45°C.

8. The preparation method according to claim 4, characterized in that: After adding 3-5% of the negative electrode binder in step (2), the temperature of the slurry is controlled to be 20-40°C.

9. The preparation method according to claim 4, characterized in that: The negative electrode binder in the step (2) is a styrene-butadiene rubber binder.

10. The preparation method according to claim 4, characterized in that: The negative electrode active material in step (2) is selected from one or both of natural graphite and artificial graphite.

11. The preparation method according to claim 4, characterized in that: The thickness of the aluminum foil in step (3) is 12 to 18 μm.

12. The preparation method according to claim 4, characterized in that: The single-sided surface density of the positive electrode slurry coated on the aluminum foil in step (3) is 200-250 g / m 2 , the upper and lower deviations are allowed to be 3g / m 2 ; Double-sided density is 400~500g / m 2 , the upper and lower deviations are allowed to be 5g / m 2 .

13. The preparation method according to claim 4, characterized in that: The thickness of the copper foil in step (3) is 7 to 11 μm.

14. The preparation method according to claim 4, characterized in that: The negative electrode slurry in step (3) is coated on the copper foil with a single surface density of 10-15 g / m 2 , the upper and lower deviations are allowed to be 3g / m 2 ; Double-sided density is 20~30g / m 2 , the upper and lower deviations are allowed to be 5g / m 2 .

15. The preparation method according to claim 4, characterized in that: The thickness of the positive electrode sheet pressed by the roller press in step (3) is 135-170 μm, with an upper and lower deviation of 2 μm allowed; the thickness of the negative electrode sheet is 150-175 μm, with an upper and lower deviation of 2 μm allowed.

16. The preparation method according to claim 4, characterized in that: The electrolyte in step (5) is an electrolyte containing LiPF6.

Citation Information

Patent Citations

  • Method for synthesizing lithium ion battery negative electrode material according to mechanochemical method

    CN103606661A

  • Nonaqueous electrolyte battery

    JP1987226560A

  • Organic electrolyte cell employing molybdenum oxide cathodic electrode

    US3808052A

  • Technology for preparing lithium ion slurry and device

    CN102569728A

  • Method for preparing positive electrode slurry of lithium ion battery

    CN103094556A

Cited By

  • Anode graphene dispersion slurry and preparation method thereof

    CN122267189A